Questioning Skill: Strategy of Developing Children’s Cognitive Aspect and Language competence. - Gomes, Fransiskus De (STKIP Santu Paulus Ruteng, 2016)
This article reviews the concept of stimulation toward children’s development aspect. Childhood isa crucial period of children development toward further stages.If children obtain good stimulation fromenvironment, their intelligence will be better improved. However, if children get poor stimulation, theirintelligence will be worse. This case brings the implication in the provision of appropriate stimulation tochildren.Stimulating the aspect of development must be carefully considered to reduce the risk on children.Questioning skill is a strategy of developing children’s cognitive aspect and language competence.It motivates children to engage in mental activities in order to get a deeper understanding.Keywords: questioning skill, strategy, developing, stimulasition, cognitive ability, language competence,children